Authenticity and Brand Sensemaking Process: A Narrative Analysis of Marketing Managers in Building Trust Through Long-Term Collaboration with Nano-Influencers - Galib, Mukhtar; Maulana; Syam, Jumiati; Muharram (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
Abstract: The strategic shift towards authenticity in digital marketing has prioritized nano-influencers to build sustainable brand trust. However, authenticity remains an ambiguous, fluid, and complex concept for marketing managers to navigate. This study aims to describe the managerial sensemaking process used to define and evaluate nano-influencer authenticity, as well as analyze the narrative strategies implemented in long-term collaborations to build brand trust. A descriptive qualitative research approach was used, through a multi-site case study method. Data were collected through in-depth interviews with marketing managers, brand managers, and social media managers. Findings indicate that managerial sensemaking towards authenticity is a nuanced qualitative process that focuses on three key dimensions: value alignment, relatable content aesthetics, and perceived intrinsic motivation, rather than solely on quantitative metrics. Strategic implementation relies on managing long-term relational partnerships that provide creative autonomy. The impact of this adaptive management is reflected in increased message credibility and community loyalty. This study concludes that structured, relational, and sensemaking-based nano-influencer partnership management can significantly increase sustainable brand trust, while offering a best practice model for marketing practitioners